Emerging chemical therapies targeting 5-hydroxytryptamine in the treatment of Alzheimer's disease. (2nd January 2017) - Calhoun, Amanda; Ko, Je; Grossberg, George T.
ABSTRACT: Introduction: Alzheimer's disease (AD) is a major neuropsychiatric disorder affecting more than 5 million Americans over age 65. By the year 2050, AD is expected to affect over 30 million. Characterized by neuronal cell death accompanied by the accumulation of neurofibrillary tangles and neuritic plaques, AD results in devastating clinical symptomatology with a lasting psychosocial and financial impact. Studies have shown that the current treatments for AD, cholinesterase inhibitors (ChEI's) and NMDA receptor antagonists, have limited efficacy. The 5-HT-6 receptor antagonists Idalopirdine and Intepirdine have shown the most progress in current clinical trials and warrant consideration as emerging treatments for AD. Areas covered: This review discusses 5-HT6 antagonists currently in clinical trials as potential treatments for AD symptomatology and how 5-HT6 physiology may play a positive role in alleviating AD symptom pathophysiology. A literature search using PubMed was conducted using the terms Idalopirdine, Intepirdine, 5-HT-6 antagonist, and AD as keywords. Clinicaltrials.gov and Alzforum were also used to obtain information on clinical trials. Expert opinion: If current Phase-3 trials are positive, 5-HT6 antagonists such as Idalopirdine and Intepirdine may be considered as supplementary treatments to ChEI's and NMDA receptor antagonists for the symptomatic treatment of AD.